Detection of Alzheimer's disease at mild cognitive impairment and disease progression using autoantibodies as blood‐based biomarkers. Issue 1 (12th April 2016) - DeMarshall, Cassandra A.; Nagele, Eric P.; Sarkar, Abhirup; Acharya, Nimish K.; Godsey, George; Goldwaser, Eric L.; Kosciuk, Mary; Thayasivam, Umashanger; Han, Min; Belinka, Benjamin; Nagele, Robert G.
Abstract: Introduction: There is an urgent need to identify biomarkers that can accurately detect and diagnose Alzheimer's disease (AD). Autoantibodies are abundant and ubiquitous in human sera and have been previously demonstrated as disease‐specific biomarkers capable of accurately diagnosing mild‐moderate stages of AD and Parkinson's disease. Methods: Sera from 236 subjects, including 50 mild cognitive impairment (MCI) subjects with confirmed low CSF Aβ42 levels, were screened with human protein microarrays to identify potential biomarkers for MCI. Autoantibody biomarker performance was evaluated using Random Forest and Receiver Operating Characteristic curves. Results: Autoantibody biomarkers can differentiate MCI patients from age‐matched and gender‐matched controls with an overall accuracy, sensitivity, and specificity of 100.0%. They were also capable of differentiating MCI patients from those with mild‐moderate AD and other neurologic and non‐neurologic controls with high accuracy. Discussion: Autoantibodies can be used as noninvasive and effective blood‐based biomarkers for early diagnosis and staging of AD.